Striving for group agency: threat to personal control increases the attractiveness of agentic groups - Stollberg, Janine; Fritsche, Immo; Bäcker, Anna (Frontiers in Psychology, 2015)
When their sense of personal control is threatened people try to restore perceived control through the social self. We propose that it is the perceived agency of ingroups that provides the self with a sense of control. In three experiments, we for the first time tested the hypothesis that threat to personal control increases the attractiveness of being part or joining those groups that are perceived as coherent entities engaging in coordinated group goal pursuit (agentic groups) but not of those groups whose agency is perceived to be low. Consistent with this hypothesis we found in Study 1 (N = 93) that threat to personal control increased ingroup identification only with task groups, but not with less agentic types of ingroups that were made salient simultaneously. Furthermore, personal control threat increased a sense of collective control and support within the task group, mediated through task-group identification (indirect effects). Turning to groups people are not (yet) part of, Study 2 (N = 47) showed that personal control threat increased relative attractiveness ratings of small groups as possible future ingroups only when the relative agency of small groups was perceived to be high. Perceived group homogeneity or social power did not moderate the effect. Study 3 (N = 78) replicated the moderating role of perceived group agency for attractiveness ratings of entitative groups, whereas perceived group status did not moderate the effect. These findings extend previous research on group-based control, showing that perceived agency accounts for group-based responses to threatened control.